Risk Communication Emergency Response Preparedness: Contextual Assessment of the Protective Action Decision Model. Issue 2 (14th June 2017) - Heath, Robert L.; Lee, Jaesub; Palenchar, Michael J.; Lemon, Laura L.
Abstract: Studies are continuously performed to improve risk communication campaign designs to better prepare residents to act in the safest manner during an emergency. To that end, this article investigates the predictive ability of the protective action decision model (PADM), which links environmental and social cues, predecision processes (attention, exposure, and comprehension), and risk decision perceptions (threat, alternative protective actions, and stakeholder norms) with protective action decision making. This current quasi‐longitudinal study of residents ( N = 400 for each year) in a high‐risk (chemical release) petrochemical manufacturing community investigated whether PADM core risk perceptions predict protective action decision making. Telephone survey data collected at four intervals (1995, 1998, 2002, 2012) reveal that perceptions of protective actions and stakeholder norms, but not of threat, currently predict protective action decision making (intention to shelter in place). Of significance, rather than threat perceptions, perception of Wally Wise Guy (a spokes‐character who advocates shelter in place) correlates with perceptions of protective action, stakeholder norms, and protective action decision making. Wally's response‐efficacy advice predicts residents' behavioral intentions to shelter in place, thereby offering contextually sensitive support and refinement for PADM.